CRITICAL READING IN TURKISH LANGUAGE CURRICULUMS - Erol DURAN (Fırat University, 2019)
An important part of learning at school are provided with readings. In order to permanent of learning is to make critical challenges. For this reason, training of critical reading education must be the most important aspect of reading education programs. This study aims to examine what kind of description and acquisitions about training of critical reading in the Turkish Language (1-5 and 6-8. classes) Curriculums. In this study, Survey model was used and content analysis was conducted. To collect data primarily, the Programs were reached from the Board of Education website (www.ttkb.meb.gov.tr). Programs were screened aspect of based on the philosophy of the curriculum and the general objectives, basic skills, methods and techniques and acquisition. According to the findings, it can be said that there are adequate and quantity acquisitions in Curriculums for both primary and secondary school students. When critical reading acquisition of the program are analyzed, it is seen that the acquisition are gained through to a text analysis studies. These acquisitions are required to discrimination, conflicts detection, wrong setting, goal setting, related to the non determination, and questioning studies to determine the similarities and differences. In this respect, these acquisitions can contribute to the training of critical reading. It can be expressed that critical reading acquisitions concentrate in elementary school 3. In first and second class of elementary schools, first priority is the development of fluent reading skills of students in grades voice. Therefore, it can be said that most of these acquisitions consider from elementary school 3 classes.